Combination of morphological and molecular data support Pestalotiopsis eleutherococci (Sporocadaceae) as a new species - Tian, Shangqing; Xu, Rong; Bhunjun, Chitrabhanu S.; Su, Wenxin; Hyde, Kevin D.; Li, Yu; Fu, Yongping; Phukhamsakda, Chayanard (Phytotaxa, 2022)
Molecular barcoding and morphological characters were used to identify a new saprotrophic species in Pestalotiopsis, which was associated with senescent leaves of Eleutherococcus brachypus (Araliaceae) in Jilin Province, China. The matrix of the internal transcribed spacer (ITS) region, translation elongation factor 1-alpha (tef1-α), and β-tubulin (tub2) were used in the maximum likelihood (ML), maximum parsimony (MP) and Bayesian inference (BI) methods. The new collections formed a distinct clade with Pestalotiopsis lijiangensis. The new species differs from P. lijiangensis by its conidial length/width ratio. Detailed description and micrographs revealed that the species is unique in its olivaceous concolorous median cells and has significantly smaller conidia compared to other related species. The position of the apical appendages of Pestalotiopsis eleutherococci are distinct and are slightly shorter while the basal appendage is slightly longer compared to P. lijiangensis. Therefore, we introduce Pestalotiopsis eleutherococci as a novel species.